The result of 1+2-4-3+4-3+3+2-44+39+2-6 has to be determined.

This is done quite simply by adding and subtracting the given numbers.

The result is -7

**1+2-4-3+4-3+3+2-44+39+2-6 = -7**

This is a problem that simply needs to have been added and subtracted as the problem goes along

1+2-4-3+4-3+3+2-44+39+2-6

The final answer would be

-7

*3 - 4 -3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6**-1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6**-4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6**-3 + 3 + 2 - 44 + 39 + 2 - 6**2 - 44 + 39 + 2 - 6**-42 + 39 + 2 - 6**-3 + 2 - 6**-1 - 6**-7*

1 + 2 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6

To solve this equation you just simply have to add and subtract

**3 - 4 -3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 **

**-1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 **

**-4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 **

**-3 + 3 + 2 - 44 + 39 + 2 - 6 **

**2 - 44 + 39 + 2 - 6**

**-42 + 39 + 2 - 6 **

**-3 + 2 - 6 **

**-1 - 6 **

**= -7**

By the order of operations, we know that we do addition and subtraction in the order we read them from left to right. So:

1 + 2 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

3 - 4 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-1 - 3 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-4 + 4 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

0 - 3 + 3 + 2 - 44 + 39 + 2 - 6 =

-3 + 3 + 2 - 44 + 39 + 2 - 6 =

0 + 2 - 44 + 39 + 2 - 6 =

2 - 44 + 39 + 2 - 6 =

-42 + 39 + 2 - 6 =

-3 + 2 - 6 =

-1 - 6 =

-7